The Relationship between Breastfeeding History and the Incindence of Picky Eating in Preschool - Abel Aprilia Putri; Ririn Muthia Zukhra; Nurhannifah Rizky Tampubolon (Indonesian Journal of Global Health Research, 2025)
Picky eater behavior is an eating problem characterized by a lack of desire to try new food variations that often occurs in preschool-aged children. Picky eaters can be influenced by many factors, one of which is the early experience of eating including breastfeeding. The introduction of various flavors through breast milk transmission can make children later become more familiar with new flavors. This study aims to determine the relationship between breastfeeding history and the incidence of picky eaters in preschool children. This study used a cross sectional approach. The sample was 157 respondents who were taken using proportionate random sampling technique at 3 kindergartens in Pekanbaru. The instruments used to obtain data on picky eater behavior in this study were Child Eating Behavior Questionnaire (CEBQ) and Breastfeeding History Questionnaire. This study used univariate and bivariate analysis with chi-square statistical test. The results of the analysis showed that there were 60 respondent children who had picky eater behavior and 97 respondent children who had non-picky eater behavior. A total of 110 respondent children have a history of exclusive breastfeeding, 4 respondent children have a history of predominant breastfeeding and 43 respondent children have a history of partial breastfeeding. The results of the chi square statistical test showed that there was a significant relationship between breastfeeding history and the incidence of picky eaters in preschool children with p value = 0.001 (< α 0.05).